(untitled) (Fiep Bulletin - online, 2013)
This study it is a quantitative and qualitative in nature, epidemiological, in which it was aimed to check whether farmers in the west of Parana are the use of personal protection equipment (PPE’s) in agricultural work. Questionnaires were applied to hundred workers (100) of the region. Being found that farmers don’t use of PPE’s, although the majority have a good level of education and have received some kind training on the importance and the correct use of them. In conclusion this way, that the PPE’s are of fundamental importance in rural activity, because they are designed to protect risks that threaten their safety and health, but farmers must be well informed and educated by a professional in the area, to avoid possible accidents at work.